Quantitative Identification of Antioxidant Basis for Dendrobium Nobile Flower by High Performance Liquid Chromatography-Tandem Mass Spectrometry - Dan Rao; Yadong Hu; Ruoxi Zhao; Hongjie Li; Ze Chun; Shigang Zheng (International Journal of Analytical Chemistry)
Dendrobium nobile is a beautiful orchid and a widely used medicinal plant. In vitro antioxidant assays suggested that D. noblie flower extracts showed significantly higher 2, 2′-azinobis-3-ethylbenzthiazoline-6-sulfonate (ABTS) and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) scavenging rates and much more ferric-reducing power than those of root, stem, leaf and fruit. To better understand the antioxidant basis of D. nobile flower, high-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) was used for metabolic identification and quantification. Finally, there were 72 metabolites among the total of 712 identified components showed significant association (coefficient >0.8, p<0.05) with ABTS scavenging rates, DPPH scavenging rates, and ferric-reducing power. The three enriched classes of flower metabolites, including amino acids and their derivatives, organic acids and their derivatives, and flavonoids, formed the main antioxidant basis. The significantly accumulated rutin, astragalin, isomucronulatol-7-O-glucoside, quercetin 4′-O-glucoside, methylquercetin O-hexoside, caffeic acid, caffeic acid O-glucoside, and p-coumaric acid (Log2(fold change) >2, p<0.01, distribution in flower >0.1%) made a key contribution to the higher antioxidant activities in flower. The relative quantification results of HPLC-MS/MS were verified by the common quantification methods. The antioxidant basis revealed of D. nobile flower will be helpful in the production of healthy or beauty products.